2009
DOI: 10.1542/peds.2008-0357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleep Deprivation on the Pediatric Electroencephalogram

Abstract: Sleep deprivation, but not sleep during the electroencephalogram, modestly increases the yield of the electroencephalogram in children diagnosed with seizures by neurologists. Compared with a routine electroencephalogram, the number needed to test with sleep-deprived electroencephalogram to identify 1 additional child with epileptiform discharges is approximately 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 25 publications
3
32
0
2
Order By: Relevance
“…In some instances EEGs were impossible to record due to an uncooperative child and in other instances the EEG was impossible to draw any conclusions from because of movement/muscle artefacts and as a consequence high impedance electrode artefacts. In literature reviews unsuccessful EEGs in children has been reported in 4-9% of the recordings which is within the limits of our observations (DeRoos et al, 2009;Olson et al, 2001;Wassmer et al, 2001b). Sander et al (2012) reported more artefacts and higher number of unsuccessful EEGs, but still not significant, in children who got melatonin prior to EEG in comparison with those who were sleep deprived.…”
Section: Discussionsupporting
confidence: 83%
“…In some instances EEGs were impossible to record due to an uncooperative child and in other instances the EEG was impossible to draw any conclusions from because of movement/muscle artefacts and as a consequence high impedance electrode artefacts. In literature reviews unsuccessful EEGs in children has been reported in 4-9% of the recordings which is within the limits of our observations (DeRoos et al, 2009;Olson et al, 2001;Wassmer et al, 2001b). Sander et al (2012) reported more artefacts and higher number of unsuccessful EEGs, but still not significant, in children who got melatonin prior to EEG in comparison with those who were sleep deprived.…”
Section: Discussionsupporting
confidence: 83%
“…Interictal discharges are seen more commonly during sleep, with the greatest activation seen during nonrapid eye movement sleep (nREM). Sleep deprivation also facilitates both epileptiform abnormalities and seizures (2,14). Recent clinical practice guidelines for EEG have supported subsequent EEG recording with sleep deprivation after a noninformative routine EEG (7,12).…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical practice guidelines for EEG have supported subsequent EEG recording with sleep deprivation after a noninformative routine EEG (7,12). A review of the literature demonstrates that EEG laboratories using only awake EEGs as routine EEG recordings report a relatively low prevalence of epileptiform discharges, whereas the higher prevalence of epileptiform discharges is seen in those with more prolonged sleep recordings (14,15). Some studies have found that sleep deprivation is more effective for producing abnormalities in EEG than sleep obtained with pharmacotherapy (15).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of relationship between sleep and epilepsy has long been observed but was first validated by Gibbs and Gibbs when they found that paroxysmal discharges occurred more frequently in sleep [8]. Therefore, often a sleep-(deprivation) EEG is performed to elicit EEG abnormalities, although the number needed to test with sleep-deprived EEG to identify one additional child with epileptiform discharges is approximately 11 [3].…”
Section: Discussionmentioning
confidence: 99%
“…In small children, this can increase the amount of information on maturation of brain electrical activity and reduces the occurrence of artifacts due to inadequate cooperation. Moreover, sleep can also increase the yield of the test itself, as for the EEG in certain epileptic syndromes [7], and this seems particularly true for EEG recordings after sleep deprivation [3].…”
Section: Introductionmentioning
confidence: 99%